Beyond cell parameters: Exploiting cell operation towards optimizing the SEI and suppressing dendrite growth on lithium metal anodes - Patino, Daisy; Dong, Bo; Villalobos, Fabian; Herrera, Steven; Bell, Jeffrey; Ozkan, Mihrimah; Ozkan, Cengiz S. (Energy storage (Hoboken, N.J. : 2019), 2020)
Lithium metal electrodes are regarded as the optimal anode for next generation lithium ion batteries especially in the lithium‐sulfur architecture. Unfortunately, the lithium metal anode falls subject to several challenges such as dendrite formation and low Coulombic efficiency, which inhibit its candidacy as a viable technology. As such, substantial research efforts alter cell parameters in effort to manipulate interfacial chemistries, mitigate dendrite growth, and improve cyclability. Unlike conventional efforts, we demonstrate a practical cell operation approach to reinforce the Solid Electrolyte Interphase in lithium anodes via a refined formation protocol governed by the redox reactions found in lithium‐sulfur systems. Galvanostatic and electrochemical impedance data on Li‐Li symmetrical cells reveal that cell operation during the formation phase plays a critical role on interface stability of lithium metal anodes. Li‐Li symmetrical cells subject to our refined protocol, P2, displayed advantages in steadily enduring high cycling currents of 6 mA with minimal polarization, and in lowering the charge transfer resistance at the cell interfaces by a fourfold when compared to cells subject to conventional formation protocols. Additionally, scanning electron microscopy images demonstrate that our formation protocol significantly minimizes the size and dispersion of lithium dendrites, as well as the degree of plated lithium. These effects are enabled by the reinforced SEI formed during P2 which offers a stable ratio between the rates of lithium intercalation to lithium deposition. Microcomputerized tomography characterization further supports these findings by revealing that P2 averts dendrite nucleation sites, and yields greater quantity of SEI species, encompassing 41.1% volume of the entire anode, compared to just 21.5% from the common formation protocol found in literature. Overall, this approach deviates from the convention of materials exploration yet highlights the importance of understanding the nature of interfacial chemistries in response to cell operation. We believe the transferability of this approach has the potential to expedite the commercialization of next‐generation lithium ion technologies.